Reduction of bacterial adhesion to biocompatible polymer surfaces via plasma processing - Moraes, Francine S. [UNESP]; Rangel, Elidiane C. [UNESP]; Lopes, Patrícia S.; Durrant, Steven F. [UNESP]; Cruz, Nilson C. [UNESP] (Begell House, 2011)
Plasma processing of the surfaces of biomaterials is interesting because it enables modification of the characteristics of a surface without affecting bulk properties. In addition, the results are strongly influenced by the conditions of the treatment. Therefore, by adjusting the plasma parameters it is possible to tailor the surface properties to best fulfill the requirements of a given application. In this work, polyurethane substrates have been subjected to sulfur hexafluoride glow discharge plasmas. The influences of different SF 6 plasma exposure times and pressures on the adhesion of Staphylococcus aureus and Pseudomonas aeruginosa to the polymer have been investigated. The wettability and surface free energy have been evaluated via contact angle measurements. At low pressure (6.7 Pa) the contact angle decreases with increasing exposure time in the 180 s to 540 s interval, but at higher pressure (13.3 Pa) it increases as a function of the same variable. Bacterial adhesion has been quantified from in vitro experiments by determining the growth of colonies on Petri dishes treated with agar nutrient. It has been observed that the surface properties play an important role in microbe adhesion. For instance, the density of adhered P. aeruginosa decreased as the surface contact angle increased. S. aureus preferred to adhere to hydrophobic surfaces. © 2011 by Begell House, Inc.
Keywords: Biocompatibility; Plasma treatment; Polymer surfaces; Pseudomonas aeruginosa; Staphylococcus aureus; Bacterial adhesion; Biocompatible polymer; Bulk properties; Exposure-time; Glow discharge plasmas; Hydrophobic surfaces; In-vitro; Low pressures; P.aeruginosa; Petri dish; Plasma exposure; Plasma parameter; S. aureus; Surface contact angle; Surface free energy; Bacteria; Biological materials; Contact angle; Glow discharges; Plasma applications; Plasma devices; Polymers; Sulfur hexafluoride; Surface chemistry; Surface properties; Adhesion; biomaterial; polymer; polyurethan; sulfur hexafluoride; bacterial growth; bacterium adherence; bacterium colony; bacterium contamination; biocompatibility; biofilm; chemical composition; contact angle; controlled study; density; disinfection; energy; exposure time; hydrophobicity; in vitro study; measurement; nonhuman; parameters; plasma gas; plasma processing; pressure; priority journal; surface property; time; wettability